Advanced Topics in Nonsmooth Dynamics Transactions of the European Network for Nonsmooth Dynamics - Leine, Remco; Acary, Vincent; Brüls, Olivier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses emerging topics in the area of nonsmooth dynamics research, such as numerical methods for nonsmooth systems, impact laws for multi-collisions, nonlinear vibrations and control of nonsmooth systems. It documents original work of researchers at the European Network for NonSmooth Dynamics (ENNSD), which provides a cooperation platform for researchers in the field and promotes research focused on nonsmooth dynamics and its applications. Since the establishment of the network in 2012, six ENNSD symposia have been organized at different European locations. The network brings together 40 specialists from 9 different countries in and outside Europe and a wealth of scientific knowledge has been gathered and developed by this group of experts in recent years. The book is of interest to both new and experienced researchers in the field of nonsmooth dynamics. Each chapter is written in such a way as to provide an introduction to the topic for researchers from other fields.
1. Comparisons of multiple-impact laws for multibody systems: Moreau's law, binary impacts, and the LZB approach -- 2. Variational analysis of inequality impact laws for perfect unilateral constraints -- 3. Periodic motions of coupled impact oscillators -- 4. Mathematical aspects of vibro-impact problems -- 5. Nonsmooth modal analysis: from the discrete to the continuous settings -- 6. Variational and numerical methods based on the bipotential and application to the frictional contact -- 7. Passive control of differential algebraic inclusions - General method and a simple example -- 8. Experimental validation of torsional controllers for drilling systems -- 9. On the constraints formulation in the nonsmooth generalized-α method -- 10. On solving contact problems with Coulomb friction: formulations and numerical comparisons.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mathematics -- Data processing; Nonlinear Optics; Multibody Systems and Mechanical Vibrations; Computational Science and Engineering; Nonlinear Optics